Clinical Review and Prognostic Analysis of α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionate Receptor-Associated Encephalitis - Wang, Kemo; Shi, Yanting; Du, Qianwen; Zhang, Ran-ran; Wu, Huaikuan; Qiao, Shan; Liu, Xuewu (Frontiers in Neurology, 2021)
Purpose: Autoimmune encephalitis (AE) is a heterogeneous neurological autoimmune disorder associated with cognitive and psychiatric symptoms. It can be divided into several subtypes based on autoantibodies. Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis (AMPAR-E) is one of the recently discovered AE subtypes, usually manifesting limbic encephalitis and with a good prognosis. Considering AMPAR-E has been described for the first time, only few cases with similar antibodies have been reported clinically. We aimed to clarify the clinical course and prognosis of the disease in the light of previous reports. Patients and methods: We collected data on the diagnosis and treatment of six cases of AMPAR-E, diagnosed at the Qilu Hospital of Shandong University in the past 5 years. We retrospectively analyzed the clinical characteristics of the patients and performed a follow-up of the disease. Results: The patients often presented with limbic encephalitis, which sometimes coexisted with tumors. In addition, immunotherapy had a significant effect on the disease. The clinical outcome was related to factors such as the age of onset, timing of treatment, and presence of tumors. Conclusion: In conclusion, specific antibody tests should be performed as early as possible in suspected cases. Clinicians should actively administer immunotherapy and the management of the co-tumor. In addition, repeat antibody tests and image examinations following discharge from the hospital guide the maintenance protocol of immunotherapy.